2013
DOI: 10.1016/j.jenvp.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

A moral basis for recycling: Extending the theory of planned behaviour

Abstract: With evidence suggesting conservation attitudes and moral norms lack discriminant validity, the study's aim was to test if this could be established for recycling, as well as how moral norms can extend the theory of planned behaviour (TPB). A sample of 271 participants that consisted predominantly of students were obtained for this correlational study (117 males and 154 females, M age = 24 years). Since confirmatory factor analysis indicated convergent validity (r = .69, p < .05), path analysis was conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
272
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(345 citation statements)
references
References 26 publications
29
272
3
2
Order By: Relevance
“…Perhaps the most important theoretical and empirical evidence presented in this study was a series of directed variables indicating that structural modeling indicates pro-social cognition with four constructs of attitude, social influence, perceived behavior control, and habit best explains travelers' pro-environmental behavioral intention. Empirical findings support the positive effect on attitude, social influence, perceived behavioral control, and habit indicating the significant variables illustrating personal behavioral intention process [15,31,[47][48][49].…”
Section: Theoretical Implicationssupporting
confidence: 53%
See 2 more Smart Citations
“…Perhaps the most important theoretical and empirical evidence presented in this study was a series of directed variables indicating that structural modeling indicates pro-social cognition with four constructs of attitude, social influence, perceived behavior control, and habit best explains travelers' pro-environmental behavioral intention. Empirical findings support the positive effect on attitude, social influence, perceived behavioral control, and habit indicating the significant variables illustrating personal behavioral intention process [15,31,[47][48][49].…”
Section: Theoretical Implicationssupporting
confidence: 53%
“…The extracting TPB values indicate attitude, and perceived behavioral control then UTAUT2 of social influence and habit. Previous studies with empirical findings support the positive effect on attitude, social influence, perceived behavioral control, and habit indicating the significant variables within TPB and UTAUT2 in illustrating the personal behavioral intention process [15,18,[47][48][49]. Chan and Bishop [48] established that personal attitude, social influence, perceived behavioral control, and habit greatly and directly affect one's behavioral intention.…”
Section: Habitmentioning
confidence: 84%
See 1 more Smart Citation
“…Other studies have also confirmed that achievement values may be as important as a predictor of attitude toward behavior (e.g. Kim (2009);Han et al (2010); Chan & Bishop (2013); Chen & Tung (2014)). …”
Section: Theoretical Contributionsmentioning
confidence: 78%
“…Specifically, the reliability coefficient for attitude was 0.850; perceived behavior control was 0.664; subjective norms were 0.831; moral norms were 0.726; and responsibility denial was 0.631. According to Chen and Bishop [61], a reliability coefficient of greater than 0.7 indicates that the measure has achieved acceptable reliability, while Kline [62] proposed reliability coefficients of around 0.8 as very good, with those between 0.7 and 0.6 as adequate. In summary, the measurement model demonstrated adequate reliability and validity.…”
Section: Latent Psychological Predictor Variablesmentioning
confidence: 99%